INTENSITAS MIELUM PADA GAMBARAN MRI SERVIKAL SEBAGAI FAKTOR PROGNOSTIK LUARAN CERVICAL SPONDYLOSIS MYELOPATHY PASCAOPERASI - Mohamad Saekhu,* Jeremia Prastya Pardede,* Renindra Ananda Aman,* Hanif Gordang Tobing, Samsul Ashar (Neurona Majalah Kedokteran Neuro Sains, 2018)
INTRODUCTION CERVICAL SPONDYLOSIS MYELOPATHY CSM IS A STENOSIS CONDITION IN CERVICAL CANAL DUE TO THE CERVICAL STRUCTURAL CHANGES THAT COMPRESS THE MYELUM THUS CAUSING SPINAL MEDULLA ISCHEMIA OTHER THAN CLINICAL FACTORS MYELUM INTENSITY CHANGES ON MRI T1WEIGHTED IMAGES T1W1 AND T2W1 MIGHT BE USEFUL TO PREDICT THE POSOPERATIVE OUTCOME